Corrosion characteristics and fuel cell performance of a cost‐effective high Mn–Low Ni austenitic stainless steel as an alternative to SS 316L bipolar plate. (17th April 2020) - Kumar, Nitish; Shaik, Gouse Peera; Pandurangan, Saravanan; Khalkho, Bhawna; Neelakantan, Lakshman; Chetty, Raghuram
Summary: In this study, newly developed high manganese (Mn) and low nickel (Ni) austenitic stainless steels were investigated as an alternative to conventionally used SS 316L for bipolar plate applications in proton exchange membrane fuel cells. Systematic studies on the corrosion behavior were carried out in simulated hydrogen and oxygen environments, for both half‐ and fuel‐cell conditions. The Mn‐based SS revealed nobler corrosion potential and comparable passive current densities to that of SS 316L. The passive current density of Mn‐based SS is well within the DoE 2020 target of <1 μA cm −2 . Though MnSS1 steel has lean Ni content, the addition of Mn and N is beneficial for improving the corrosion performance, which is comparable to SS 316L. The recorded ICR values for Mn SS1 and SS 316L are 234.6 ± 20 and 155 ± 20 mΩ cm 2 at a compaction force of 140 N cm −2, respectively. Both the steels do not to meet the DoE ICR target of 10 mΩ cm 2, which requires conductive coating or improvement in oxide conductivity. The performances of the steels (both Mn‐SS and 316L SS) with varying thickness were also investigated in a single fuel cell condition with serpentine flow field design as bipolar plates with varying thickness (10, 5 and 2 mm). A maximum power density of 370 mW cm −2 was achieved with the Mn‐based metallic bipolar plates, whereas SS 316L showed 354 mW cm −2 . By changing the composition of austenitic stainless steel, that is, using Mn SS1 instead of SS 316L the overall fuel cell cost decreases by three times. Highlights: Low cost Mn as an alternative to Ni for the role of austenite stabilizer is utilized to lower the overall cost of metallic bipolar plate. Addition of N to the alloy also helps in improving the corrosion properties. An optimum amount of Mn and N shifts the E corr to noble direction as compared to conventional 316L in simulated fuel cell conditions. The peak power density of the new alloy is similar to 316L bipolar plate. The base material prior to any surface modification can be modified to improve its corrosion resistance in PEMFC conditions. Abstract : High Mn–Low Ni austenitic stainless steel (SS) is used as an alternative to conventional 316L SS for bipolar plate application in proton exchange membrane fuel cell (PEMFC). The developed SS showed comparable corrosion characteristics as SS 316L. The fuel cell performance of the Mn SS bipolar plates showed a slightly higher peak power density (370 mW cm −2 ) compared to SS 316L (354 mW cm −2 ). The developed steel could be a low‐cost option for bipolar plate applications in PEMFC.